(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The main aim of the paper is mainly to exhibit that these focal points are very much related to all different kinds of social issues, which are expressed in the book of the name, Arvind Adiga’s Between the Assassinations. This research showed that the social issues as well as the problems are never very prominent and significant but these right treatments or conducts are needed for certain social issues, which are very much prominent in this Between the Assassinations.Adiga represented the contemporary and the modern India. He also represented the social as well as political milieu. And he represented this modern India by providing various kinds of examples which include different types of gross malpractices, which are still practiced in the democratic. This research found out that any message in this novel mainly focuses on misery as well as poverty of India. It also explained all the religious as well as socio-political of the contemporary India.